AYAT MAKKIYAH DAN MADANIYAH SERTA IMPLIKASI TERHADAP PENAFSIRAN QUR’AN - depri, deprizon (Fakultas Studi Islam Universitas Muhammadiyah Riau, 2022)
ABSTRACT This study examines and explores the Makkiyah and Madaniyah verses, the Al-Qur'an is the word of God which was revealed to the Prophet Muhammad SAW. The Qur'an is an eternal miracle unlike the miracles of the previous Prophets. As we have seen, the Qur'an was received by Rasulullah SAW within a period of 23 years, namely some were revealed when the Apostle was in Mecca and some were revealed when the Apostle was in Medina. Therefore, in general, the scholars of rahmatahumullahu divide the Qur'an into two parts: Makkiyah and Madaniyah. Makkiyah is a revelation that was revealed to the Prophet Muhammad before emigrating to Medina. Madaniyah is a revelation that was revealed to the Prophet Muhammad after emigrating to Medina. Methodology This research refers to the literature approach (library research which is descriptive qualitative). This study focuses on the object of study in the form of written theoretical sources. The results of this research, especially for the academic world, can be used as reference material and references (literature) that can add to the library's treasures, especially in the field of Islamic education. Keywords: Verses of the Qur'an, Makkiyah and Madaniyah.